Brief, low frequency stimulation of rat peripheral C-fibres evokes prolonged microglial-induced central sensitization in adults but not in neonates. - Hathway, G; Vega-Avelaira, D; Moss, A; Ingram, R; Fitzgerald, M (2009)
The sensitization of spinal dorsal horn neurones leads to prolonged enhancement of pain behaviour and can be evoked by intense C-fibre stimulation, tissue inflammation and peripheral nerve injury. Activation of central immune cells plays a key role in establishing pain hypersensitivity but the exact nature of the afferent input that triggers the activation of microglia and other glial cells within the CNS, remains unclear. Here intense but non-damaging, electrical stimulation of intact adult rat C-fibres for 5 min at 10 Hz induced central sensitization characterized by significant decreases in mechanical withdrawal thresholds 3, 24 and 48 h later. This maintained (>3 h) hypersensitivity was not observed following topical skin application of capsaicin. C-fibre evoked sensitization was accompanied by significant microglial activation, shown by increased Iba-1 immunoreactivity throughout the dorsal horn at 24 and 48 h and significant upregulation of markers of microglial activation: IL-6 and Mcp-1 at 3h and Mmp3, CSF-1 and CD163 at 24 and 48 h. C-fibre stimulation caused no nerve damage at ultrastructural and molecular levels. Lower intensity stimulation that did not activate C-fibres or sham stimulation did not increase Iba-1 immunoreactivity or induce behavioural sensitivity. Pre-treatment with minocycline (40 mg/kg, i.p.) prevented the C-fibre evoked sensitization and microglial activation. Identical C-fibre stimulation in 10-day old rat pups failed to activate microglia or change behaviour. These results demonstrate that a brief period of low frequency C-fibre stimulation, in the absence of nerve damage, is sufficient to activate microglia resulting in behavioural hyperalgesia.